PRINSIP NON-INTERVENSI DAN PERLINDUNGAN HAM: KRISIS DIPLOMATIK ARAB SAUDI-KANADA - Aprilia, Shely; Ronaboyd, Irfa (Faculty of Law, Universitas Tanjungpura, 2026)
The diplomatic conflict between Saudi Arabia and Canada in 2018 drew significant attention in international law, as it emerged from Canada’s public criticism delivered through social media of the arrest of human rights activists in Saudi Arabia, which the Saudi government perceived as interference in its domestic affairs. This study aims to analyze the dynamics of bilateral relations between Saudi Arabia and Canada with regard to the application of the principle of non-intervention and the protection of human rights within the framework of international law. This research employs an empirical juridical approach, using data collection techniques including interviews, observation, and literature study on international legal instruments and contemporary sources such as official government statements, social media posts, and international news coverage from 2018 to 2023. An interview was conducted with a Saudi national as a social witness to public responses surrounding the rhetorical escalation between the two states. The findings indicate that Canada’s public call for the release of human rights activists does not, in itself, constitute prohibited intervention under international law, although the use of imperative language created a perception of coercion from the Saudi perspective. The tension between state sovereignty and the universality of human rights is shown to be contextual and shaped by broader geopolitical dynamics. The restoration of diplomatic relations in 2023 demonstrates that peaceful settlement, bilateral dialogue, and multilateral diplomacy remain the most effective mechanisms for navigating normative conflicts between non-intervention and human rights protection Abstrak Konflik diplomatik antara Arab Saudi dan Kanada pada tahun 2018 menjadi perhatian dalam hukum internasional karena memunculkan ketegangan yang bermula dari kritik terbuka Pemerintah Kanada terhadap penahanan aktivis HAM di Arab Saudi melalui media sosial, yang kemudian dianggap sebagai bentuk intervensi dalam urusan domestik oleh Pemerintah Saudi. Penelitian ini bertujuan untuk menganalisis dinamika hubungan bilateral antara Arab Saudi dan Kanada terhadap pelaksanaan prinsip non-intervensi dan perlindungan hak asasi manusia dalam konteks hukum internasional. Penelitian ini menggunakan pendekatan yuridis empiris, dengan teknik pengumpulan data berupa wawancara, observasi, serta studi kepustakaan terhadap instrumen hukum internasional dan sumber-sumber aktual seperti pernyataan resmi pemerintah, unggahan media sosial, serta pemberitaan internasional terkait periode 2018–2023. Wawancara dilakukan dengan seorang warga negara Arab Saudi sebagai saksi sosial atas respons publik terhadap eskalasi retorika kedua negara. Hasil penelitian menunjukkan bahwa seruan publik Kanada mengenai pembebasan aktivis HAM tidak serta-merta memenuhi unsur intervensi yang dilarang dalam hukum internasional, meskipun diksi yang bersifat imperatif menimbulkan persepsi koersif bagi Arab Saudi. Ketegangan kedua prinsip kedaulatan dan universalitas HAM, menunjukkan bahwa batas keduanya bersifat kontekstual dan dipengaruhi dinamika politik global. Pemulihan hubungan diplomatik pada tahun 2023 membuktikan bahwa penyelesaian secara damai, dialog bilateral, dan diplomasi multilateral tetap menjadi mekanisme paling efektif dalam menavigasi konflik normatif antara non-intervensi dan penegakan HAM.